Korean Through Folktales - Yoon, KyungAh (Open textbook library., 2017)
Korean Through Folktales consists of four chapters and each centers on a famous Korean folktale. The lessons and values that famous folktales teach are embedded and permeated in various aspects of the Koran culture. Using folktales in the curriculum will provide an engaging way to expose students to a slice of the target culture that native Koreans are naturally exposed to at an early age. Through the selected folktales and various activities offered in the book, students can gain cultural knowledge and insights into traditional and cultural values while they are given linguistic lessons to reinforce their acquired skills and to apply the learned materials in an integrated approach. Korean Through Folktales is designed to accompany 1st-year, 2nd-year, and 3rd-year Korean courses offered at Portland State University. However, any Korean teacher can adopt this book to supplement his/her course materials at elementary, intermediate, and advanced levels. There are four chapters in the book. Each chapter will note main themes of a widely known folktale introduced in the chapter, followed by the links to several videos to watch and get a gist or a background of the story. The ensuing section will introduce important elements and symbolism embedded in the story so as to provide insights and to enhance the depth of appreciation. After that, three versions of the folktale are presented for different levels, followed by grammar lessons, exercises, and tasks. Traces of folktales and allusions to them are evident in cultural products that many students enjoy, such as dramas, movies, and music. Therefore, knowledge in folktales will help students make cultural connections as well as enrich their experience of learning the Korean language.